2020
DOI: 10.1186/s12885-020-6695-9
|View full text |Cite
|
Sign up to set email alerts
|

High tumor budding is a strong predictor of poor prognosis in the resected perihilar cholangiocarcinoma patients regardless of neoadjuvant therapy, showing survival similar to those without resection

Abstract: Background: Tumor budding (TB) is used as an indicator of poor prognosis in various cancers. However, studies on TB in perihilar cholangiocarcinoma are still limited. We examined the significance of TB in resected perihilar cholangiocarcinoma with or without neoadjuvant therapy. Methods: Seventy-eight patients who underwent surgical resection at our institution for perihilar cholangiocarcinoma from 2004 to 2017, (36 with neoadjuvant therapy), were enrolled in this study. TB was defined as an isolated cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…15 Unfortunately, the staging numbers did not correspond to the severity of the tumor. 16 Recently, unremitting efforts were taken to optimize prognostic models in PHC [17][18][19] ; however, the using linear approaches are challenging to model the complexity of tumour non-linear relationships with barely satisfactory discrimination. Genomic investigation of potential prognostic biomarker is rapidly developed, but still lacks certain clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…15 Unfortunately, the staging numbers did not correspond to the severity of the tumor. 16 Recently, unremitting efforts were taken to optimize prognostic models in PHC [17][18][19] ; however, the using linear approaches are challenging to model the complexity of tumour non-linear relationships with barely satisfactory discrimination. Genomic investigation of potential prognostic biomarker is rapidly developed, but still lacks certain clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the frequency of regional lymph node metastasis was three‐fold greater in patients with high‐budding tumors than in patients with low‐ and intermediate‐budding tumors. Previous reports also suggest that tumor budding is associated with lymph node metastasis in patients with ICC or perihilar cholangiocarcinoma 21,24 . Namely, patients with metastatic lymph nodes who did not undergo lymphadenectomy might be identified as T4N0, which is the same as patients with stage IVA showing T1‐3N1 disease.…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports also suggest that tumor budding is associated with lymph node metastasis in patients with ICC or perihilar cholangiocarcinoma. 21 , 24 Namely, patients with metastatic lymph nodes who did not undergo lymphadenectomy might be identified as T4N0, which is the same as patients with stage IVA showing T1‐3N1 disease.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, indication of curative-intent surgery should be carefully performed by prolonging preoperative therapy as a watch and wait approach. Additionally, our recent study demonstrated that high tumor budding (TB) can be a novel poor prognostic factor in resected perihilar cholangiocarcinoma regardless of neoadjuvant therapy [33] as well as various type of cancers such as esophageal [34] and pancreas [35]. However, the TB cannot be evaluated before surgery.…”
Section: Discussionmentioning
confidence: 99%